Lasting Effects: Seven Year Results of the Castrop Nomogram for Femtosecond Laser-Assisted Paired Corneal Arcuate Incisions. (1st February 2022) - Wendelstein, Jascha A.; Hoffmann, Peter C.; Schwarzenbacher, Luca; Fischinger, Isaak R.; Hirnschall, Nino; Menapace, Rupert; Langenbucher, Achim; Findl, Oliver; Bolz, Matthias
ABSTRACT: Purpose: Long-term results of arcuate incisions are rarely reported. This is unfortunate as long-term stability of astigmatic correction is of great interest to surgeons performing astigmatic correction. This study investigates the 7 year stability of results after application of femtosecond laser-assisted arcuate incisions with the Castrop nomogram. Methods: Prospective interventional case series at the Augen- und Laserklinik, Castrop-Rauxel, Germany. Single site, single surgeon study. Seven year results of cataract patients with low to moderate corneal astigmatism receiving femtosecond laser‐assisted arcuate incisions using a TechnolasVictus SW 2.7 (Bausch & Lomb Inc, Dornach, Germany) were assessed and compared to 1 year results. Outcome evaluation was based on astigmatic vector analysis, manifest refraction, and visual acuity. Results: The study analyzed 19 eyes of 19 patients 7 years after surgery. Ocular residual astigmatism changed from −0.26 to −0.39 D. Preoperative corneal astigmatism was −1.51 D. Correction Index changed from 1.0 to 1.16. The magnitude of difference vector changed from 0.26 to 0.39 D. The index of success changed from 0.20 to 0.29. Spherical equivalent remained stable. A slight tendency to change toward astigmatic overcorrection was mainly observed for patients with preoperative with the rule astigmatism, but not with patients with against the rule astigmatism. Conclusions: The Castrop nomogram showed stable results 7 years after surgery. Similar to toric IOL surgery, it is advisable to be less aggressive when correcting with the rule astigmatism, to avoid overcorrection over a long period.